2019
DOI: 10.3390/w11081608
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis-Assisted Mn(II)/Sulfite Process for Organic Contaminant Degradation at Near-Neutral pH

Abstract: Manganese-catalyzed sulfite activation (i.e., Mn(II)/sulfite) has emerged as an advanced oxidation process to produce sulfate radical (SO4•−) for water treatment. However, to maintain the catalytic activity of Mn(II) ion, solution acidity has to be kept below pH 4, which is difficult to maintain in practice. Moreover, Mn(II)/sulfite reaction is a strongly oxygen-dependent process, and purging air into reaction solution is another extra cost. To solve the above issues, we devised to implement electrolysis into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Sulfite has low toxicity, and its median lethal dose (LD 50 ) to animals can reach 3560 mg/kg, which is 3 times that of persulfate (802 mg/kg). 24 Second, as a byproduct of desulfurization, 25 sulfite is inexpensive, which can save cost in practical applications. Studies have shown that using transition metals (Cu, 26 Cr, 27 Fe, 28,29 Co, 30 Mn, 31 etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfite has low toxicity, and its median lethal dose (LD 50 ) to animals can reach 3560 mg/kg, which is 3 times that of persulfate (802 mg/kg). 24 Second, as a byproduct of desulfurization, 25 sulfite is inexpensive, which can save cost in practical applications. Studies have shown that using transition metals (Cu, 26 Cr, 27 Fe, 28,29 Co, 30 Mn, 31 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Finding a new environmentally friendly and inexpensive alternative to replace persulfate has become a new research focus. Sulfite has low toxicity, and its median lethal dose (LD 50 ) to animals can reach 3560 mg/kg, which is 3 times that of persulfate (802 mg/kg) . Second, as a byproduct of desulfurization, sulfite is inexpensive, which can save cost in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…1d). MBS may react as SO3 2− under Fenton conditions (the Fentonlike reactivity of sulfite is shown in several studies) (Jia et al 2019), but MBS is a more effective way to add sulfite to the system. Sulfite is actually unstable in aqueous solution in the presence of oxygen; therefore, the presence of high concentrations of SO3 2− from the very start could trigger degradation/auto-oxidation reactions.…”
Section: Evidence Suggests That the Active Species Is An S-based Radi...mentioning
confidence: 99%